MENGOPTIMALKAN KINERJA KARYAWAN SEKTOR LOGISTIK: PERAN DOMINAN LINGKUNGAN KERJA DAN STIMULAN SISTEM PENGHARGAAN - Staghita Herdiana; Teguh Wicaksono; Amalia Wahyuni (PT. Hasba Edukasi Mandiri, 2026)
This study aims to analyze the influence of reward systems and work environment on employee performance at PT. Cipta Krida Bahari (CKB Logistik) Banjarmasin. The research employed a quantitative approach using a survey method. Data were collected through questionnaires distributed to 82 employees selected using a saturated sampling technique. Data analysis was conducted using multiple linear regression with the assistance of SPSS software. The results indicate that both reward systems and work environment have a positive and significant effect on employee performance. An effective reward system can enhance employee motivation and performance, while a safe and comfortable work environment contributes to higher work productivity. Simultaneously, both variables significantly affect employee performance. The coefficient of determination shows that reward systems and work environment explain 35.1% of the variation in employee performance, while the remaining percentage is influenced by other factors outside the research model. These findings suggest that improving reward systems and creating a conducive work environment are essential strategies for enhancing employee performance.